Understanding the Origins of Populist Political Parties and the Role of External Shocks - Eugenio Levi; Isabelle Sin; Steven Stillman (Institute of Labor Economics (IZA), 2021)
We use electoral survey data to examine the impact that two large external shocks had on the development of New Zealand First (NZF), one of the oldest populist parties in the OECD. We find that structural reforms, which led to large negative impacts on particular locations, and immigration reforms, which led to large spatially concentrated increases in skilled migration, both increased voting for NZF in its first years of existence. These shocks led to changes in political attitudes and policy preferences and had persistent effects on voting for NZF even twenty years later. Overall, they play an important role in explaining the rise of populism in NZ. Understanding how these shocks led to the development of NZF is particularly relevant for thinking about how populism has been extending its reach in the 2010s.
Keywords: D72; P16; H40; 330; populism; political parties; trade; immigration; shocks